Eye Movements and Strategy Shift in Skill Acquisition: Adult Age Differences - Touron, Dayna R. (Oxford University Press, 2011)
OBJECTIVES. The current article explores age differences in skill acquisition. We validated strategy self-reports, evaluated whether eye movements may be automatic as well as information seeking, and considered the contribution of eye movements to age differences in overall performance. METHODS. Young and older adults performed the noun-pair lookup (NP) task. With practice, pairs (e.g., IVY-BIRD) in a lookup table can be verified by memory rather than by visual search. Trials used (1) standard stimuli, (2) memory tests without the lookup table, or (3) memory tests with a table filled with uninformative placeholders. RESULTS. For standard trials, reported scanning was associated with more table gazes, relative to reported retrieval. The lookup table was occasionally fixated during reported retrieval, particularly by older adults, but the table target pair was no more likely to be gazed than other table pairs. For memory probes, older adults also gazed the lookup table when filled with placeholders, indicating that eye movements can represent attentional capture rather than information seeking. DISCUSSION. Strategy self-reports in the NP task can be considered valid measures of strategy use. However, unnecessary automatic eye movements that appear to influence older adults’ NP task performance cannot be identified by strategy reports alone.